Nutqiy muloqot jarayinida bog‘lovchilarning pragmatik xususiyatlari namoyon bo‘lishi - Usmonova, Umida; Aslam, Usmonov (FILOLOGIYA UFQLARI JURNALI, 2022)
Usmanov Aslam and Usmanova Umida's article "Pragmatic features of connectives in the process of speech communication" provides information on the use of connectors in the types of speech communication and their formation of pragmatic meaning. The article discusses and scientifically analyzes the pragmatic features of the use of connectors in communication.